Milk to Mandalay: dairy consumption, animal history and the political geography of colonial Burma - Saha, Jonathan (Journal of historical geography, 2016)
British imperial writers in Burma regularly moaned about milk. They complained about the difficulties they faced acquiring it in the colony. They were selfconscious about how their consumption of it might be viewed by the Burmese population, who predominantly did not drink cow's milk. And they worried about the quality of the supply provided by itinerant Indian dairymen, who they viewed as being neglectful and insanitary. Through these concerns the absence of milk became a marker of the colony's difference from the rest of the Raj. At the same time, the colonial government came to recognise the importance of locally-bred working cattle for Burmese agriculture. In their attempts to protect these valuable nonhuman labourers, Indian dairy herds were represented as a problem breed that threatened the indigenous stock. The threat from foreign cattle coalesced around epizootic disease and uncontrolled crossbreeding. These concerns were coterminous with official and nationalist anxieties about the Indian human population in the colony. Building on recent scholarship uncovering more-than-human geographies, this article reveals how colonial policies designed to improve the dairy industry and protect Burmese cattle contributed to the material and imaginative territorialisation of Burma, and its eventual separation from British India. •Shows that imperial perceptions of milk consumption were entangled in colonial imagined geographies.•Uncovers how the vulnerabilities and capacities of cattle made them political subjects.•Demonstrates how attitudes to Indian cattle were linked to concerns over Indian migration.•Emphasises the more-than-human aspects of colonial Burma's political geography.